Female Leadership in the Communities of the Khlysty (Flagellants) and Skoptsi (Eunuchs), 17th to Early 20th Centuries - Yeremieiev, Pavlo; Shevchenko, Oleksandr (The Journal of V. N. Karazin Kharkiv National University. Series History, 2024)
The article sets out to outline the genesis of female leadership in the sects of the Khlysty (Flagellants) and Skoptsi (Eunuchs); find whether its nature changed during the period from the mid-17th to the early 20th centuries; define the types of female leadership in these religious communities; compare its characteristics between the two sects; and trace the mutual influence between the social practices of female leadership and the folklore tradition of the ‘mystical sects.’ The study draws on the principles of gender history. The source base includes both texts produced within the sects and ‘external’ testimony, such as records of state authorities and the official church, works by early Old Believer leaders, and ethnographic observation. The author argues that female leadership among the Khlysty was made possible by their radical rejection of marriage and was closely connected with the gradual strengthening of the role of Virgin Mary in Khlysty folklore. Three types of female leadership among the Khlysty and Skoptsi are distinguished. The first type can be defined through the identification of the leader with the Mother of God, and the second type presupposed community leadership and belief in the special mystical abilities of women, but without conferring on the leader the status of ‘the Mother of God.’ The third type was temporary leadership, in which only at certain moments a woman uttered prophecies that the congregation perceived as the voice of the Holy Spirit. In the period from the mid-17th to early 18th centuries, the institution of Khlysty ‘Mothers of God’ already existed, and in some Khlysty communities women played an important role in cult practices. Most recorded instances of fully independent women leaders among the Khlysty occur in the period from the late 1710s to the middle of the 18th century, primarily because of the spread of Khlysty beliefs in the church milieu, particularly in women’s monasteries. From the mid-18th century on, we can observe a rapid decline of the practice of fullfledged female leadership among the Khlysty and Skoptsi. This is due to the elimination of the most prominent female leader figures, as well as to the fact that at this time monasteries as sectarian centers were almost completely replaced by villages, which were characterized by conservative views and traditional family relations.